2018
DOI: 10.1016/j.theriogenology.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Conception risk of beef cattle after fixed-time artificial insemination using either SexedUltra™ 4M sex-sorted semen or conventional semen

Abstract: The objective of this study was to compare conception rates of female beef cattle inseminated at a fixed-time with either conventional (CON) or SexedUltra™ sex-sorted (SU) semen. Treatments included CON or SU with two sires represented within each treatment. Cows (n = 316) and heifers (n = 78) from six locations were randomly assigned treatment. Ovulation was synchronized in all females using the industry-standard 7-d CO-Synch + controlled internal drug release (CIDR) protocol (100 μg GnRH + CIDR [1.38 g proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
9
0
4
Order By: Relevance
“…The results of these studies are inconclusive. Conception rates using sex-sorted sperm for AI have either been reported to be similar 34 , 35 , or significantly reduced in heifers 9 , 10 , 36 , 37 and lactating cows 18 , 19 , 38 41 when using sex-sorted sperm for AI. Further to that, the effects of refinements of the sex-sorting technology such as the introduction of SexedULTRA™ 17 , 18 , 35 , have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies are inconclusive. Conception rates using sex-sorted sperm for AI have either been reported to be similar 34 , 35 , or significantly reduced in heifers 9 , 10 , 36 , 37 and lactating cows 18 , 19 , 38 41 when using sex-sorted sperm for AI. Further to that, the effects of refinements of the sex-sorting technology such as the introduction of SexedULTRA™ 17 , 18 , 35 , have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Conception rates using sex-sorted sperm for AI have either been reported to be similar 34 , 35 , or significantly reduced in heifers 9 , 10 , 36 , 37 and lactating cows 18 , 19 , 38 41 when using sex-sorted sperm for AI. Further to that, the effects of refinements of the sex-sorting technology such as the introduction of SexedULTRA™ 17 , 18 , 35 , have not been fully elucidated. Thus, this study is the first to perform a comprehensive analysis of the reproductive performance of bovine sex-sorted sperm, covering all studies performed from the beginning of the commercialization until to date, spanning from 1999 to 2021 (22 years).…”
Section: Introductionmentioning
confidence: 99%
“…Sex‐sorted semen is an innovative technology to sustain a dairy farm economically profitable. Male calves generally have a little economic income in the dairy herds; thus, the use of sex‐sorted semen is preferred for increasing the number of female calves which are used as replacement heifers afterwards (Cottle, Wallace, Lonergan, & Fahey, 2018; Crites et al., 2018). Besides, several studies have reported that sex‐sorted semen increases economic profitability (Chebel, Guagnini, Santos, Fetrow, & Lima, 2010) and that sex‐sorted semen technology had also considerable benefits such as acceleration genetic gain (Hohenboken, 1999), enhanced herd biosecurity (Cottle et al., 2018), lower animals participating in the progeny test (De Vries et al., 2008) and reduction in the incidence of dystocia (Holden & Butler, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy rates are 60 to 80% of the conventional sperm range or higher 17,18 , especially with the use of the recently developed SexedULTRA TM technology which included increasing the number of sperm per insemination from 2 to 4 million 19,20 . However, increasing the number of sexed-sperm per insemination dose is unable to fully compensate and restore the reduced conception rate [20][21][22] . With regards to in vitro fertilization (IVF) and in vitro production (IVP) of embryos, the use of sexed-sperm results in variable blastocyst rates, ranging from 36% to 52% and subsequent pregnancy rates ranging from 26% to 40% 23,24 .…”
mentioning
confidence: 99%